Microbial and host immune factors as drivers of COPD. Issue 3 (3rd July 2018) - Mika, Moana; Nita, Izabela; Morf, Laura; Qi, Weihong; Beyeler, Seraina; Bernasconi, Eric; Marsland, Benjamin J.; Ott, Sebastian R.; von Garnier, Christophe; Hilty, Markus
Compartmentalisation of the respiratory tract microbiota in patients with different chronic obstructive pulmonary disease (COPD) severity degrees needs to be systematically investigated. In addition, it is unknown if the inflammatory and emphysematous milieux in patients with COPD are associated with changes in the respiratory tract microbiota and host macrophage gene expression. We performed a cross-sectional study to compare non-COPD controls (n=10) to COPD patients (n=32) with different disease severity degrees. Samples (n=187) were obtained from different sites of the upper and lower respiratory tract. Microbiota analyses were performed by 16S ribosomal RNA gene sequencing and host gene expression analyses by quantitative real-time PCR of distinct markers of bronchoalveolar lavage cells. Overall, the microbial communities of severe COPD (Global Initiative for Chronic Obstructive Lung Disease (GOLD) grade 3/4) patients clustered significantly differently to controls and less severe COPD (GOLD 1/2) patients (permutational multivariate ANOVA (MANOVA), p=0.001). However, we could not detect significant associations between the different sampling sites in the lower airways. In addition, the chosen set of host gene expression markers significantly separated COPD GOLD 3/4 patients, and we found correlations between the composition of the microbiota and the host data. In conclusion, this study demonstrates associations between host gene expression and microbiota profiles that may influence the course of COPD. Associations of the host immune response and a disordered microbiota in patients with different COPD severity degrees http://ow.ly/h2mW30k9Nua